2017
DOI: 10.1177/0011128717693215
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Variation in Prior Record Penalties Across Conviction Offenses

Abstract: The focal concerns perspective suggests that criminal history and the nature of the offense interact to influence judicial assessments of community threat, yet this question has not been subject to systematic empirical examination. Drawing on 4 years of data (2007-2010) from the Pennsylvania Commission on Sentencing ( N = 75,676), we utilize linear quantile mixed models (LQMM) to examine the impact of prior record on the conditional distribution of sentence lengths across violent, property, drug, and sex offen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(115 reference statements)
1
3
1
Order By: Relevance
“…Overall, this research contributes to the literature on societal and criminal justice responses to persons convicted of sexual crimes, observing that contextual factors indicative of both the focal concerns and populist punitiveness perspectives have differential effects when individuals convicted of sexual crimes are the subject of judicial discretion. That is, rather than judges drawing on a particular set of explanatory factors when sentencing aggregate groups, our findings are consistent with certain groups conditioning the effects of covariates operating at both the individual and contextual levels (Cassidy & Rydberg, 2018; Lin et al, 2012; Ulmer, 2012). The specific contextual effects on sentencing for persons convicted of sexual crimes that were observed here are consistent with the notion that judges consider these individuals as distinct risks necessitating special decision making (Bumby & Maddox, 1999), for instance, enhancing penalties in small court contexts and reducing the salience of caseload pressure in the incarceration decision.…”
Section: Resultssupporting
confidence: 72%
“…Overall, this research contributes to the literature on societal and criminal justice responses to persons convicted of sexual crimes, observing that contextual factors indicative of both the focal concerns and populist punitiveness perspectives have differential effects when individuals convicted of sexual crimes are the subject of judicial discretion. That is, rather than judges drawing on a particular set of explanatory factors when sentencing aggregate groups, our findings are consistent with certain groups conditioning the effects of covariates operating at both the individual and contextual levels (Cassidy & Rydberg, 2018; Lin et al, 2012; Ulmer, 2012). The specific contextual effects on sentencing for persons convicted of sexual crimes that were observed here are consistent with the notion that judges consider these individuals as distinct risks necessitating special decision making (Bumby & Maddox, 1999), for instance, enhancing penalties in small court contexts and reducing the salience of caseload pressure in the incarceration decision.…”
Section: Resultssupporting
confidence: 72%
“…The substantive utility of quantile regression is the capability to identify patterns of variation in sentencing disparity as one moves from relatively short to relatively long sentences (Britt, 2009). Although prior research shows punishment disparities are more often found in incarceration decisions than sentence length decisions (Chiricos & Crawford, 1995; Spohn, 2000; Wang, Mears, Spohn, & Dario, 2013), our findings indicate that quantile regression is capable of uncovering additional disparity that may be obscured via more traditional methods of examining sentence length outcomes (see also Cassidy & Rydberg, 2018; Rydberg, Cassidy, & Socia, 2018). Most importantly, to advance theoretical development and provide context to empirical findings, more qualitative research is needed to better understand the ways in which judges think about sentencing decisions.…”
Section: Discussioncontrasting
confidence: 66%
“…2 Our analyses focus on first-time felony convictions (N = 1,014,646). This focus was strategic because it limited the influence of unobserved confounders on sentencing and add-ons decisions that can be introduced by defendants who have lengthy prior records or regularly cycle through the local court system (see, generally, Cassidy & Rydberg, 2018;Crow, 2008). Excluding defendants with prior felony records arguably allows for more accurate estimates of race, ethnicity, and add-on effects.…”
Section: Methodsmentioning
confidence: 99%